Pengaruh Karakteristik Sasaran Penganggaran terhadap Kinerja Manajerial dengan Ketidakpastian Tugas sebagai Pemoderasi (Studi pada Kantor Pemerintah Provinsi di Sulawesi Utara) - Mathar, Mudassir (Jurnal Aplikasi Manajemen, 2011)
This study aims to prove empirically, the relationship between variables in the study include: participation in budget preparation, clarity of budget targets, the budget target difficulty, feedback, budgeting, task uncertainty and managerial performance. The research was conducted through surveys of government officials who work in the province of North Sulawesi. The unit of analysis is the individual government official who worked on the local work unit (SKPD). Study sample of 126 respondents. Census sampling method. The test data is done by using statistical analysis of multiple linear regression analysis, MRA (Moderated Regression Analysis) / test and F test i test used to test the effect of partially independent variables against the dependent variable. F test used to test the simultaneous effect of independent variables on the dependent variable. MRA (Moderated Regression Analysis) is used to test whether the variable pemoderasi able to moderate the relationship between the independent variables with the dependent variable. The results prove that the nine hypotheses are proposed as the initial allegations of research answered with a positive and significant results for all research purposes. The results also showed that the uncertainty task to strengthen the influence of participation in budget preparation, budget goal clarity, goal difficulty budgeting, budgeting feedback on Managerial Performance.